Storage of Text Messages on e-Book Files using Least Significant Bit and Haar Wavelet Method - Hasanudin, Muhaimin; Kuswoyo*, Deni (Aceh International Journal of Science and Technology, 2021)
Peak discharge information is indispensable for flood control planning by taking into account the physiographic factors of the watershed. Flood occurs because the capacity of the watershed and river channels is smaller than the flood discharge. One of the causes of rivers' reduced flood flow capacity is vegetation cover and land use that cannot store rainfall. Thus, this paper aims to determine the peak discharge from the watershed's physical characteristics and land-use changes by comparing the river storage capacity in the Krueng Seunagan watershed. The rational method is used to calculate the peak discharge. Some of the data used in this study are the shapefile map provided by Geospatial Information Agency, land use, rainfall, soil types, and Landsat 8 OLI/TIRS digital imagery. Analysis of the physical characteristics of the watershed consists of morphology and morphometry. Land use in the area of the Krueng Seunagan watershed increased the peak discharge during the observation year (2003-2017). Besides the land-use factor, discharge is also influenced by high rainfall intensity and runoff coefficient obtained from land use analysis. In the Krueng Seunagan watershed area, the C value obtained was 0.0505 0.0720, indicating that the Krueng Seunagan watershed area was classified as good or harmless. The river flow density of 0.53 belongs to the medium category. The river flow increases and decreases in the flood water level, which is neither too fast nor too slow. The roundness index of the Seunagan watershed of 1.0004 indicates that the basins are widened or circular and, consequently, the rate and volume of surface runoff are fast. Krueng Seunagan watershed runoff coefficient increased by 42.51% and rainfall intensity by 37.05%, while discharge increased by 95.31%. The discharge capacity that the Krueng Seunagan River Basin can accommodate from the measurement results in the downstream watershed is 158.47 m3/sec. While the peak discharge using the rational method gets a value that varies in each year of observation from (2003-2017). The peak discharge value in 2003 amounted to 183.52 m3/sec, and the highest in 2017 amounted to 358.44 m3/sec. This shows that the river holding capacity in the Krueng Seunagan watershed will not accept the amount of peak discharge, and consequently, the flood will always occur.